Effects of employment protection and product market regulations on the Italian labor market - Adriana D. Kugler; Giovanni Pica (Institute for the Study of Labor (IZA), 2003)
Labor market regulations have often been blamed for high and persistent unemployment in Europe, but evidence on their impact remains mixed. More recently, attention has turned to the impact of product market regulations on employment growth. This paper analyzes how labor and product market regulations interact to affect turnover and employment. We present a matching model which illustrates how barriers to entry in the product market mitigate the impact of labor market deregulation. We, then, use the Italian Social Security employeremployee panel to study the interaction between barriers to entry and dismissal costs. We exploit the fact that costs for unjust dismissals in Italy increased for firms below 15 employees relative to bigger firms after 1990. We find that the increase in dismissal costs after 1990 decreased accessions and separations in small relative to big firms, especially for women. Moreover, consistent with our model, we find evidence that the increase in dismissal costs had smaller effects on turnover for women in sectors faced with strict product market regulations.
Keywords: J65; L43; L11; J63; E24; 330; barriers to entry; costs of unjust dismissals; European unemployment; Markteintritt; Regulierung; Kündigungsschutz; Kosten; Beschäftigungseffekt; Arbeitslosigkeit; Schätzung; Theorie; Italien